Online communities as childcare resources among households with young children in metropolitan areas in Japan - Mikoto Kukimoto (Netcom)
This paper examines the relation between the the role of the use of the Internet, online communities, and households with young children. As parentiyoung networks have changed the Internet has been drawing attention as a source for providing childcare information and for networking with other parents. Since the 1990s, the deregulation of childcare services has increased the importance of immediate and abundant childcare information. The online community for households with young children has great importance in metropolitan areas in Japan.